Root Resorption in Orthodontics - Furkan Dindaroğlu; Servet Doğan (Galenos Yayinevi, 2016)
Root resorption has been the subject of many studies, and it can be caused by many factors such as the mechanics used during orthodontic treatment, factors related to the type and magnitude of the force, and other factors related to treatment such as the type of tooth movement and malocclusion. The clinical importance of root resorption is directly related to its detectability. Therefore, orthodontic and biological factors that may cause root resorption were evaluated using various imaging methods in present use. In this review, root resorption in orthodontics was considered from different viewpoints.